Characterization of the regulation and function of zinc‐dependent histone deacetylases during rodent liver regeneration12. Issue 5 (23rd April 2013) - Huang, Jiansheng; Barr, Emily; Rudnick, David A.
Abstract: The studies reported here were undertaken to define the regulation and functional importance of zinc‐dependent histone deacetylase (Zn‐HDAC) activity during liver regeneration using the mouse partial hepatectomy (PH) model. The results showed that hepatic HDAC activity was significantly increased in nuclear and cytoplasmic fractions following PH. Further analyses showed isoform‐specific effects of PH on HDAC messenger RNA (mRNA) and protein expression, with increased expression of the class I HDACs, 1 and 8, and class II HDAC4 in regenerating liver. Hepatic expression of (class II) HDAC5 was unchanged after PH; however, HDAC5 exhibited transient nuclear accumulation in regenerating liver. These changes in hepatic HDAC expression, subcellular localization, and activity coincided with diminished histone acetylation in regenerating liver. The significance of these events was investigated by determining the effects of suberoylanilide hydroxyamic acid (SAHA, a specific inhibitor of Zn‐HDAC activity) on hepatic regeneration. The results showed that SAHA treatment suppressed the effects of PH on histone deacetylation and hepatocellular bromodeoxyuridine (BrdU) incorporation. Further examination showed that SAHA blunted hepatic expression and activation of cell cycle signals downstream of induction of cyclin D1 expression in mice subjected to PH. Conclusion : The data reported here demonstrate isoform‐specific regulation of Zn‐HDAC expression, subcellular localization, and activity in regenerating liver. These studies also indicate that HDAC activity promotes liver regeneration by regulating hepatocellular cell cycle progression at a step downstream of cyclin D1 induction. (HEPATOLOGY 2013)